2010
DOI: 10.4103/0970-4388.73784
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the effect of topical fluorides on the microhardness of various restorative materials: An in vitro study

Abstract: The use of 1.23% APF gel may be detrimental to the long-term durability of glass ionomer restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 1 publication
0
12
0
3
Order By: Relevance
“…Unfortunately, APF gel includes hydrofluoric and phosphoric acids that have the ability to accelerate the degradation of the glass particles and can enhance the surface roughness of restorative materials. [29][30][31] In contrast, Botta et al 16 reported that APF gel decreased the surface roughness of microhybrid composite resin and resinmodified GIC. Also, the surface roughness of the nanofilled composite resin was not influenced by APF gel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, APF gel includes hydrofluoric and phosphoric acids that have the ability to accelerate the degradation of the glass particles and can enhance the surface roughness of restorative materials. [29][30][31] In contrast, Botta et al 16 reported that APF gel decreased the surface roughness of microhybrid composite resin and resinmodified GIC. Also, the surface roughness of the nanofilled composite resin was not influenced by APF gel.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, topical fluoride agents may lead to surface deterioration on restorative materials. 15,16 Especially, acidulated phosphate fluoride (APF) gels which contain a strong acid can increase the surface roughness of restorative materials, 17 thereby enhancing the surface area available for bacterial adhesion. 18,19 This may decrease the clinical durability of the restorative materials.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, vários estudos demonstraram que o flúor gel atua tanto na estrutura dentária quanto no material restaurador, modificando a micromorfologia da superfície do material, deixando-o mais rugoso, além de levar à perda da dureza do material, corroborando aos resultados encontrados referentes ao tratamento com gel de fluorfosfato acidulado a 1,23% (9,12,13,14). A degradação promovida pela aplicação do flúor gel fosfato acidulado é provavelmente causada pela lixiviação dos cátions Na, Ca e Al que formam a matriz e a formação de complexos com os ânions ácidos (15).…”
Section: Discussionunclassified
“…Isso se deve ao fato de que o flúor fosfato acidulado contém ácido fosfórico na sua composição e que é responsável por condicionar as partículas de vidro e liberar os principais cátions constituintes da matriz, provocando erosão química do material com dissolução da sua superfície, diminuindo a longevidade da restauração (9,20). Estudos de BENDERLI, GOKÇE, KASAKM (11) e GILL & PATHAK (14) demonstraram que quando há a presença de monômeros resinosos na estrutura do material ocorre possivelmente uma diminuição dos efeitos erosivos do gel de flúor fosfato acidulado, corroborando aos resultados relativos ao Vitremer. Nos cimentos resinosos modificados por resina, a reação de polimerização ácido-base é complementada por uma segunda reação fotoativada ou quimicamente ativada.…”
Section: Discussionunclassified
See 1 more Smart Citation